Cerebral Microembolization During Aortic Valve Replacement Using Minimally Invasive or Conventional Extracorporeal Circulation: A Randomized Trial. Issue 12 (10th June 2016) - Basciani, Reto; Kröninger, Felix; Gygax, Erich; Jenni, Hansjörg; Reineke, David; Stucki, Monika; Hagenbuch, Niels; Carrel, Thierry; Eberle, Balthasar; Erdoes, Gabor
Abstract: To compare intraoperative cerebral microembolic load between minimally invasive extracorporeal circulation (MiECC) and conventional extracorporeal circulation (CECC) during isolated surgical aortic valve replacement (SAVR), we conducted a randomized trial in patients undergoing primary elective SAVR at a tertiary referral hospital. The primary outcome was the procedural phase‐related rate of high‐intensity transient signals (HITS) on transcranial Doppler ultrasound. HITS rate was used as a surrogate of cerebral microembolism in pre‐defined procedural phases in SAVR using MiECC or CECC with (+F) or without (−F) an oxygenator with integrated arterial filter. Forty‐eight patients were randomized in a 1:1 ratio to MiECC or CECC. Due to intraprocedural Doppler signal loss ( n  = 3), 45 patients were included in final analysis. MiECC perfusion regimen showed a significantly increased HITS rate compared to CECC (by a factor of 1.75; 95% confidence interval, 1.19–2.56). This was due to different HITS rates in procedural phases from aortic cross‐clamping until declamping [phase 4] ( P  = 0.01), and from aortic declamping until stop of extracorporeal perfusion [phase 5] ( P  = 0.05). Post hoc analysis revealed that MiECC−F generated a higher HITS rate than CECC+F ( P  = 0.005), CECC−F ( P  = 0.05) in phase 4, and CECC−F ( P  = 0.03) in phase 5, respectively. In open‐heart surgery, MiECC is not superior to CECC with regard to gaseous cerebral microembolism. When using MiECC for SAVR, the use of oxygenators with integrated arterial line filter appears highly advisable. Only with this precaution, MiECC confers a cerebral microembolic load comparable to CECC during this type of open heart surgery.